Anthracnose on Cucurbits in Florida - Pamela D. Roberts; Gary Vallad; Shouan Zhang; Nicholas Dufault; Mathews Paret (EDIS)
Watermelon (Citrullus lanatus), cantaloupe or muskmelon (Cucumis melo), squash (Cucurbita pepo), bitter gourd (Momordica charantia), and cucumber (Cucumis sativa) are commonly grown  throughout Florida on both commercial farms and home gardens, while pumpkin (Cucurbita maxima) production is largely limited to north Florida.  Anthracnose on cucurbits, caused by the fungus Colletotrichum orbiculare, is a common disease that occurs worldwide and throughout Florida. While all cucurbits are susceptible to the disease, cucumber, cantaloupe, and watermelon are most frequently affected. This EDIS document provides information regarding the pathogen, disease cycle, diagnostics and symptoms, and an overview of management of this disease on cucucurbits.